THE URGENCY OF UNIVERSITAS REPUBLIK INDONESIA AS A HOLDING UNIVERSITY TOWARD GOLDEN INDONESIA 2045 - K.P. Suharyono S. Hadiningrat; Teguh Yuwono; Trismawan Djonisajoko; Endang Haerudin; Budi Kalimantoro (JIPOWER : Journal of Intellectual Power, 2026)
This descriptive qualitative study argues that the establishment of Universitas Republik Indonesia (URI) represents a strategic institutional breakthrough for reconstructing national human-resource governance through a public-sector holding-university model. The proposed role of URI is to integrate fragmented leadership-development systems, reduce sectoral silos, and strengthen governance capacity for sustainable national development. Using a qualitative-comparative approach, the study benchmarks four elite leadership and public-sector education institutions in France, Russia, Japan, and China: INSP, RANEPA, The Matsushita Institute of Government and Management, and the Chinese Academy of Governance. The synthesis produces a proposed Penta-Helix Leadership Integration Model linking academia, state-owned enterprises and business, civil and military institutions, civil society, and mass media. Tactical implementation includes a residential National Common Core Program for cross-sector leadership candidates, a 20% affirmative quota for disadvantaged, frontier, and outermost regions (3T), and an algorithm-based profile-matching placement system. The study further recommends that URI be legally positioned through a special sui generis Government Regulation so that it can operate as an integrated national leadership-development platform aligned with Asta Cita, the 2025–2029 RPJMN, and the Golden Indonesia 2045 vision.